2020
DOI: 10.24205/03276716.2020.97
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Features and Social-Psychological Mechanism of Participants in Group Events Induced by Environmental Damage

Abstract: The rapid economic growth in China has led to a decline in environmental quality. The environmental damage has undermined the interests of some people, causing a number of group events. Considering the key factors of environmental damage, this paper explores the psychological features of the participants in the group events induced by environmental damage, and probes deep into the social psychological mechanism of such events. On this basis, the authors put forward a solution to the group events caused by envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…This study reviewed various theories and empirical studies and came to have an empirical based theory/model that integrates both economic and non-economic factors. This model supported scholars that confirmed that economic growth does not fully depends on the economic variables (physical resources) but also are mediated/depends on noneconomic variables such as psychological resources and political stability or governance quality (Suh and Choi, 2018;Yi, 2020;Twenge, Martin and Campbell, 2018;Srivastava and Agarwal, 2020;Malhotra, 2020).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…This study reviewed various theories and empirical studies and came to have an empirical based theory/model that integrates both economic and non-economic factors. This model supported scholars that confirmed that economic growth does not fully depends on the economic variables (physical resources) but also are mediated/depends on noneconomic variables such as psychological resources and political stability or governance quality (Suh and Choi, 2018;Yi, 2020;Twenge, Martin and Campbell, 2018;Srivastava and Agarwal, 2020;Malhotra, 2020).…”
Section: Discussionsupporting
confidence: 72%
“…In general it is evidenced that, only economic variables are not sufficient to mould an optimal economic growth model (Li and Shi, 2019;Kara and Petrescu, 2018;Huggins, Thompson and Obschonka, 2018;Braganza, Chen, Canhoto, and Sap, 2020;Markussen et al 2018;Di Maria, Peronic and Sarracino, 2017;Marhaenia and Purnamawati, 2021;Yi, 2020;Fehder et al 2018). Moreover, adequately concrete theoretical and empirical evidences confirm that non-economic variables are positively impact economic growth (Roka, 2020;Semeijn, et al 2020;Meyer and Hamilton, 2020;Stevenson and Wolfers, 2013;Asadullah, Xiao and Yeoh, 2016;Loon, Otaye-Ebede and Stewart, 2019;Bhuiyan and Ivlevs, 2019;Charles, Wu and Wu, 2019;Wiklund, Nikolaev,Shir, Foo and Bradley, 2020).…”
Section: Background Of the Studymentioning
confidence: 99%
See 2 more Smart Citations